Potential for synthesis and degradation of extracellular matrix proteins by valve interstitial cells seeded onto collagen scaffolds. - Dreger, SA; Thomas, P; Sachlos, E; Chester, A; Czernuszka, J; Taylor, P; Yacoub, M (2006)
Matrix remodeling, which involves proteolytic enzymes, such as the matrix metalloproteinases (MMPs), is of significant importance with respect to tissue engineering a heart valve construct. The ability of valve interstitial cells (ICs) to release these enzymes in biological scaffolds and to synthesize their own matrix has not been adequately studied, and this has important implications for tissue engineering. Cultured human aortic valve ICs were seeded onto a 3-dimensional type I collagen matrix for 28 days, whereby the presence of the remodeling enzymes, MMPs, were determined using immunohistochemistry, and detection of extracellular matrix (ECM) gene expression was performed using in situ hybridization. The collagenases, stromelysins, and membrane-type MMPs were expressed in 1%, 2%, and 5% collagen scaffolds after 28 days, whereas gelatinase expression was not observed. In situ hybridization revealed the presence of the ECM messenger ribonucleic acid (mRNA) in cells cultured in collagen scaffolds however, an increase in all three mRNAs was only detected in the 1% collagen scaffolds. The presence of collagenases, stromelysins, and membrane-type MMPs indicate that human valve ICs have the capacity to remodel type I collagen scaffold and that the genes necessary for synthesizing matrix have been turned on within the cells themselves. Scaffold composition also demonstrated differential effects onMMPexpression. These observations are of relevance with respect to the development of tissue-engineered heart valves.